Hyperspectral scanning laser optical tomography - Chen,L; Li,G; Tang,L; Zhang,M; Liu,L; Liu,A; McGinty,J; Ruan,S (Journal of Biophotonics, 2019)
In order to study physical relationships within tissue volumes or even organism-level systems, the spatial distribution of multiple fluorescent markers needs to be resolved efficiently in three dimensions. Here, rather than acquiring discrete spectral images sequentially using multiple emission filters, a hyperspectral scanning laser optical tomography system is developed to obtain hyperspectral volumetric data sets with 2-nm spectral resolution of optically transparent mesoscopic (millimeter-centimeter) specimens. This is achieved by acquiring a series of point-scanning hyperspectral extended depth of field images at different angles and subsequently tomographically reconstructing the 3D intensity distribution for each wavelength. This technique is demonstrated to provide robust measurements via the comparison of spectral and intensity profiles of fluorescent bead phantoms. Due to its enhanced spectral resolving ability, this technique is also demonstrated to resolve largely overlapping fluorophores, as demonstrated by the 3D fluorescence hyperspectral reconstruction of a dual-labeled mouse thymus gland sample and the ability to distinguish tumorous and normal tissues of an unlabeled mouse intestine sample.